2015
DOI: 10.1111/bju.13326
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based assessment of cancer‐specific mortality after local tumour ablation or observation for kidney cancer: a competing risks analysis

Abstract: After adjustment for comorbidity and tumour characteristics in elderly patients with kidney cancer, LTA was associated with a clinically and statistically significant protective effect on CSM, compared with OBS. This advantage of LTA deserves consideration when obtaining informed consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Thermal ablation might be a superior alternative to active surveillance even in older and frail patients (22). However, recent results by Kokabi et al (13) suggested that despite these recommendations, thermal ablation might be underused in eligible populations.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal ablation might be a superior alternative to active surveillance even in older and frail patients (22). However, recent results by Kokabi et al (13) suggested that despite these recommendations, thermal ablation might be underused in eligible populations.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lane BR et al [20], although no difference was observed in cancer-specific mortality between AS and NSI (PN and TA), there were apparent differences in characteristics of patients and tumors between the comparing groups, and the proportion of malignancy in AS might be diluted to an unknown extent. Nevertheless, a study by Larcher A et al [17] mentioned that after adjustment for other cause mortality and various characteristics of patients and tumors, TA seemed to be associated with a protective effect on cancer specific mortality when compared with observation, and resulted in acceptable peri-operative morbidity [21]. We also noted that PN demonstrated better OS than AS, while TA did not.…”
Section: Discussionmentioning
confidence: 60%
“…Seven studies addressed to CSS, of which two were studies of the SEER dataset [17, 18]. The combined HR of these studies revealed that NSI was associated with a statistically significant CSS benefit compared with AS for patients with renal masses (HR = 0.64, 95%CI: 0.46–0.89, P < 0.001) with apparent inter-study heterogeneity ( I 2 = 54%, Chi 2 = 13.10, P = 0.04) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, some studies have reported clinical outcomes to 5 years. Cancer-specific survival after IGTA of T1a RCC ranges from 96% to 100% with a weighted mean of 97% (15,22,23,68,69,76). The threshold for cancer-specific survival of IGTA for T1a RCC is 94%.…”
Section: Discussionmentioning
confidence: 99%